Effects of Non-insulin Anti-hyperglycemic Agents on Gut Microbiota: A Systematic Review on Human and Animal Studies - Cao, Thao T. B.; Wu, Kun-Chang; Hsu, Jye-Lin; Chang, Chih-Shiang; Chou, Chiahung; Lin, Chen-Yuan; Liao, Yu-Min; Lin, Pei-Chun; Yang, Liang-Yo; Lin, Hsiang-Wen (Frontiers in Endocrinology, 2020)
Background: As growing evidence links gut microbiota with the therapeutic efficacy and side effects of anti-hyperglycemic drugs, this article aims to provide a systematic review of the reciprocal interactions between anti-hyperglycemic drugs and gut microbiota taxa, which underlie the effect of the gut microbiome on diabetic control via bug-host interactions. Method: We followed the PRISMA requirements to perform a systematic review on human versus animal gut microbiota data in PubMed, SCOPUS, and EMBASE databases, and used Cochrane, ROBIN-I, and SYRCLE tools to assess potential bias risks. The outcomes of assessment were trends on gut microbiota taxa, diversity, and associations with metabolic control (e.g., glucose, lipid) following anti-hyperglycemic treatment. Results: Of 2,804 citations, 64 studies (17/humans; 47/mice) were included. In human studies, seven were randomized trials using metformin or acarbose in obese, pre-diabetes, and type 2 diabetes (T2D) patients. Treatment of pre-diabetes and newly diagnosed T2D patients with metformin or acarbose was associated with decreases in genus of Bacteroides, accompanied by increases in both Bifidobacterium and Lactobacillus. Additionally, T2D patients receiving metformin showed increases in various taxa of the order Enterobacteriales and the species Akkermansia muciniphila. Of seven studies with significant differences in beta-diversity, the incremental specific taxa were associated with the improvement of glucose and lipid profiles. In mice, the effects of metformin on A. muciniphila were similar, but an inverse association with Bacteroides was reported. Animal studies on other anti-hyperglycemic drugs, however, showed substantial variations in results. Conclusions: The changes in specific taxa and β-diversity of gut microbiota were associated with metformin and acarbose in humans while pertinent information for other anti-hyperglycemic drugs could only be obtained in rodent studies. Further human studies on anti-hyperglycemic drugs other than metformin and acarbose are needed to explore gut microbiota’s role in their therapeutic efficacies and side effects.